HUBUNGAN PENGETAHUAN IBU HAMIL TENTANG KELAS IBU HAMIL DENGAN MOTIVASI MENGIKUTI KELAS IBU HAMIL DI PUSKESMAS 2 MANDIRAJA KABUPATEN BANJARNEGARA - Chasanah, Uswatun; ., Ratifah (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2013)
ABSTRACT: CORELATION ABOUT KNOWLEDGE OF PREGNANT WOMEN ABOUT ANTENATAL CLASS PREGNANCY WITH MOTIVATION PREGNANT WOMEN FOLLOW ANTENATAL CLASS PREGNANCY IN REGION HEALT CENTRES OF SUBDISTRICT MANDIRAJA OF REGENCY BANJARNEGARA: Antenatal Class of pregnancy is a means to learn about health care for pregnant women, in the form of face to face in the group are expected to increase the knowledge and skills of pregnant women about pregnancy, but the problem is the prevalence of pregnant women following the arrival of a class of pregnant women is very low (46%), it can be influenced by the knowledge and motivation. Good knowledge of the influence behavior and encourage an interest in or motivation of pregnant mothers attend classes. Objective: This study aims to determine whether there is a relationship between maternal knowledge about the class of pregnant women with the motivation of pregnant mothers attend classes. Method: The method used in this study is a quantitative method with the cross sectional approach. Samples in this study as many as 76 respondents taken by total sampling. This study using the Spearman Rank Test Statistics. Result: Most respondents have sufficient knowledge of the number 32 people (42.1%) and most well motivated as many as 32 people (42.1%). Most of the knowledge of both the motivation of both the 16 (69.5%), with sufficient knowledge of good motivation 16 people (50%) and lack of knowledge of good motivation 21 people (61.9%). Conclusion: No association between maternal knowledge about the class of pregnant women with the motivation of pregnant mothers attend classes. Suggestion: Need reach wider to generalize the results of research and the need to consider other variables associated with motivation pregnant women attend classes.Keywords: Knowledge, Motivation, Classroom Pregnant Women